Implementation of Handmade Credit Agreements (Without Notary Deed) - Rikha Farikhatul Fitriani; Taufan Fajar Riyanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The complete study, entitled